Sensitivity of PCR Assays for Murine Gammaretroviruses and Mouse Contamination in Human Blood Samples - Lee, Li Ling; Lin, Lin; Bell, David S.; Levine, Susan; Hanson, Maureen R. (PloS one, 2012)
Gammaretroviruses related to murine leukemia virus (MLV) have variously been reported to be present or absent in blood from chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) patients and healthy controls. Using subjects from New York State, we have investigated by PCR methods whether MLV-related sequences can be identified in nucleic acids isolated from whole blood or from peripheral blood mononuclear cells (PBMCs) or following PBMC culture. We have also passaged the prostate cancer cell line LNCaP following incubation with plasma from patients and controls and assayed nucleic acids for viral sequences. We have used 15 sets of primers that can effectively amplify conserved regions of murine endogenous and exogenous retrovirus sequences. We demonstrate that our PCR assays for MLV-related gag sequences and for mouse DNA contamination are extremely sensitive. While we have identified MLV-like gag sequences following PCR on human DNA preparations, we are unable to conclude that these sequences originated in the blood samples.